A Novel Anti‐Coagulative Nanocomplex in Delivering miRNA‐1 Inhibitor Against Microvascular Obstruction of Myocardial Infarction. Issue 11 (27th April 2020) - Hong, Ting; Wei, Yazhong; Xue, Xiaomei; Li, Yongyong; Dong, Haiqing; Guo, Xiaoyu; Shi, Xueyin; He, Bin
Abstract: Great progress has been made in miRNA nanodelivery for the treatment of myocardial infarction (MI). However, miRNA nanodelivery within the infarct is impeded by microvascular obstruction as a local circulatory disorder caused by microthrombus formation in microvessels. Knowing that low molecular weight heparin (LMWH) can effectively prevent microthrombus formation in microcirculation, it is hypothesized whether surface modification of the nanocarrier with LMWH can overcome microvascular obstruction in the infarct area for better miRNA delivery. Herein, a novel nanocomlex consisting of dendrigraft poly‐l ‐lysine (DGL)‐loaded miR‐1 inhibitor as the core to decrease apoptosis of cardiomyocytes and LMWH as the shell to overcome microvascular obstruction of the infarct area is developed. The results show that this anti‐coagulative nanocomlex is able to reduce microthrombus formation in microvessels and inhibit blood‐coagulation factor Xa, thereby overcoming microvascular obstruction in the infarct area. In addition, it further enhances the uptake of miR‐1 inhibitor within the infarct and decreases myocardiocyte apoptosis, thus improving the cardiac function and attenuating the myocardial fibrosis. In conclusion, modification of DGL‐loaded miR‐1 inhibitor with LMWH helps overcome microvascular obstruction in delivering the drug to the infarct area, thus providing a promising therapeutic strategy for achieving a better therapeutic outcome of MI. Abstract : A novel nanoparticle consisting of dendrigraft poly‐l ‐lysine‐loaded miR‐1 inhibitor as the core to decrease apoptosis of cardiomyocytes and LMWH as the shell to overcome microvascular obstruction of the infarct area is develped. As expected, this nanoparticle with anticoagulative capacity achieves a better therapeutic outcome in the treatment of myocardial infarction.